Relationship Between Storage and Recording with Quality of DPT Vaccine Cold Chain in Puskesmas - Faradiba Hikmarida (Universitas Airlangga, 2014)
An increase in diphtheria cases in Sidoarjo District and there are cases with the status of being immunized against Diphtheria Pertussis Tetanus (DPT) indicate a problem with the immunization program. The success of immunization depends on the quality of the vaccine provided. DPT vaccine cold chain that is less can reduce the quality of the DPT vaccine. This study aims to analyze the closeness between DPT vaccine storage and recording of DPT vaccine cold chain and DPT vaccine cold chain quality at the Public health center (PHC) of Sidoarjo District. This research is a descriptive study with a cross-sectional research design. The sample size used is the total population, that is all PHC in Sidoarjo District are 26 PHC. The variables studied were storage, recording, and quality of DPT vaccine cold chain. The results showed that DPT vaccine storage was classified as good (58%), cold chain recording of DPT vaccine was lacking (77%) and the quality of the DPT vaccine cold chain in the PHC was classified as good (62%). The Spearman correlation test showed that the closeness between DPT vaccine storage and the quality of the DPT vaccine cold chain in the PHC was strong and positive (r=0.561). The closeness between the recording of the DPT vaccine cold chain with the quality of the DPT vaccine cold chain at the PHC was moderate and positive (r=0.421). The better DPT vaccine storage and DPT vaccine cold chain recording the better the quality of the DPT vaccine cold chain. It is necessary to improve the compliance of officers in terms of storing and recording cold chain DPT vaccines in PHC in accordance with procedures.